I can make dolls' clothes : easy-to-follow patterns to make clothes and accessories for your favorite doll - Scott-Smith, Louise, 1968-; Vaux, Georgia (Thames & Hudson, 2015)
"Sew chic new doll's outfits with some fabric scraps, a few sequins and a button. Follow actual-size patterns, which are quick and easy to make. Includes super-clear instructions for beginners, with tips and tricks along the way. Patterns fit all popular 12 inch fashion dolls"--